Connections, Questions, Controversies, and the Potential Paths Forward. Issue 159 (17th September 2018) - Nicolaides, Aliki; Scully‐Russ, Ellen
Abstract: In this final chapter, we identify and elaborate the connections throughout the volume. We explore the philosophical underpinnings of the original model and analyze how the different lenses in these chapters lead the authors to new understandings of informal and incidental learning that trouble some of the features of the original model. We examine how these different lenses impact informal and incidental theory, practice, and research.